Concussion in Motorsport? Experience, Knowledge, Attitudes, and Priorities of Medical Personnel and Drivers. Issue 6 (November 2020) - Adams, Stephanie A.; Turner, Anthony P.; Richards, Hugh; Hutchinson, Peter J.
Abstract : Objective: To assess concussion experiences, knowledge, and attitudes of motorsport medical personnel and drivers and to determine priority areas regarding concussion within the sport. Design: Sequential mixed-method design. Part 1: stakeholder interviews; part 2: cross-sectional online survey. Setting: United Kingdom. Participants: Part 1: key motorsport stakeholders (N = 8); part 2: motorsport medical personnel and drivers (N = 209) representing amateur and/or professional 4-wheeled motorsport. Main Outcome Measures: Concussion experience, knowledge, attitudes, and perceived priority areas. Results: Thirty-one percent of surveyed drivers (age = 37.91 ± 13.49 years: 89% male) reported suffering from concussion in motorsport. Eighty-seven percent of surveyed medical personnel (age = 48.60 ± 10.68 years: 74% male) reported experience with concussed drivers, and 34% reported feeling pressured to clear a driver with concussion. Gaps in knowledge and misperceptions about concussion were reported in both groups, and disparity between concussion attitudes emerged between drivers and medical personnel. Application of assessment and management procedures varied between medical personnel and there was evidence motorsport policy and concussion guidelines may not be directly followed. According to both medical personnel (77%) and drivers (85%), "education and training" is the top priority area for the sport. Conclusions: There is clear evidence of concussions in motorsport, but accurate knowledge about this injury is missing. Concussion education and training for all drivers and medical personnel is required. Additional investigations into concussion attitudes are advised to complement and advance simple educational initiatives. Further investigation is also required to determine how to best support motorsport medical personnel, and general practitioners, who hold significant responsibility in guiding drivers from diagnosis to return to racing, and to support the effective implementation of policy. Abstract : Supplemental Digital Content is Available in the Text.